Effect of Profitability, Leverage, and Corporate Social Responsibility on Tax Avoidance - Dithaloka Suryono; Sutandi Sutandi (Fakultas Bisnis, 2022)
Tax avoidance is one of the factors, tax avoidance is a legal tax planning activity, namely by looking for loopholes from tax rules. This study aims to test whether Profitability (ROA), Leverage (DAR), and Corporate Social Responsibility (CSR) have an effect on tax avoidance. In this study, tax avoidance is proxied by CETR. The data used in this study is secondary data. The population of this study is manufacturing companies in the various industrial goods sector listed on the Indonesia Stock Exchange for the 2017-2019 period. The method used for determining the sample is purposive sampling in accordance with predetermined criteria and obtained a sample of 12 companies for a period of three consecutive years so as to obtain a total sample of 36 companies. Data analysis using multiple linear analysis test. The results of this study indicate that Corporate Social Responsibility has a significant negative effect on tax avoidance, while Profitability and Leverage have no effect on tax avoidance.